A multisectoral and multidisciplinary endeavor: a review of diabetes self-management apps in China - Meifang Chen; Daniel Weissglass; Chengyi Li; Di Li; Zixuan Wu; Li Zhang (BMC Public Health, 2023)
Abstract Background While the use of self-management apps has considerable promise to efficiently reduce the diabetes burden that disproportionally affects low- and middle-income countries (LMICs), and the multisectoral and multidisciplinary approaches have been encouraged to be used in diabetes management, little is known about the status of the integration of these approaches in the existing diabetes self-management apps. This review examines the diabetes apps in China as an indication of the current status of integrating multisectoral and multidisciplinary approaches in diabetes mHealth care in LMICs. Methods Eligible diabetes apps were searched on major Chinese app stores up to December 23, 2022. The app comprehensiveness index (ranging 0–80) regarding the app functions and diabetes management domains was created. The multisectoral and multidisciplinary features were summarized using indices derived from current guidance. Results Sixty-six apps were reviewed, all developed by private companies. The average comprehensiveness score was 16, with many major self-management domains and functions not represented among the reviewed apps. Forty apps (61%) involved multiple sectoral entities, with public/private and private/private collaborations being the most common collaborative combinations. Thirty-seven apps (56%) involved multiple disciplines, among which endocrinology/metabolism, nutrition, and cardiovascular medicine were the top three most common disciplines. Compared to non-multidisciplinary apps, multidisciplinary apps tended to provide more comprehensive services in apps (6.14 vs. 5.18, p = 0.0345). Different sectors and disciplines tended to work independently, without robust interactions, in providing diabetes management services in the reviewed apps. Conclusion Multisectoral and multidisciplinary features has presented in the current diabetes self-management apps in China; however, it is still in its infancy and significant limitations existed. More engagement of civil society organizations and community groups and innovative collaborations between sectors and disciplines are needed to provide comprehensive, continuous, and patient-centered mHealth care for patients with diabetes in LMICs like China. Clear guidance for integrating and evaluating the multisectoral and multidisciplinary efforts in self-management apps is necessary to ensure the effective use of mHealth solutions for diabetes management in LMICs.